Double blind crossover comparison of the effects of dual chamber pacing (DDD) and ventricular rate adaptive (VVIR) pacing on neuroendocrine variables, exercise performance, and symptoms in complete heart block. Issue 4 (April 1991) - Oldroyd, K G; Rae, A P; Carter, R; Wingate, C; Cobbe, S M
Abstract : OBJECTIVE--To compare the effects of dual chamber pacing (DDD) and ventricular rate adaptive pacing (activity sensing) (VVIR) in patients with complete heart block. DESIGN--Double blind crossover comparison with one month in each pacing mode. PATIENTS--10 consecutive patients aged 23-74 presenting with complete anterograde atrioventricular block at rest and on exercise and with an intact atrial rate response received Synergyst I (Medtronic) pacemakers. MAIN OUTCOME MEASURES--Symptom scores, maximal exercise performance on a treadmill, and the plasma concentrations of atrial natriuretic peptide, adrenaline, and noradrenaline. RESULTS--No significant differences were identified between pacing modes in symptom scores for dyspnoea, fatigue, and mood disturbance; exercise time; and maximal oxygen consumption. One patient with intact ventriculoatrial conduction developed pacemaker syndrome during VVIR pacing. Resting plasma concentrations of atrial natriuretic peptide were raised in complete heart block and were restored to normal by DDD pacing but not by VVIR pacing. Resting plasma catecholamine concentrations were normal in complete heart block and in both pacing modes. During exercise the increase in the concentrations of all three hormones was similar in both pacing modes. CONCLUSIONS--In patients with complete anterograde and retrograde atrioventricular block, symptoms and maximal exercise performance were no better during DDD than during VVIR pacing.